ENHANCING OF PRESERVICE CHEMISTRY TEACHERS’ SELF-EFFICACY THROUGH THE PREPARATION OF PEDAGOGICAL CONTENT KNOWLEDGE IN VOCATIONAL CONTEXT - Antuni Wiyarsi (Pendidikan Kimia Unimus, 2018)
Pedagogical Content Knowledge (PCK) development of appropriate chemistry in vocational context is necessary to prepare the capability of pre-service chemistry teachers in designing effective chemistry learning in vocational schools. This study aims to assess the self-efficacy pre-service chemistry teachers by the learning based on PCK development in vocational context. Pretest-posttest control group design was used in these research. The results showed that the PCK development strategy in the vocational context is able to increase self-efficacy of pre-service chemistry teachers. Most of pre-service chemistry teachers have increased self-efficacy, although some of pre-service teachers have decreased self-efficacy. The main implication of this research is the need for restructuring of the curriculum for pre-service chemistry teacher education programs that are more concerned with professional development in the context of vocational schools